2019
DOI: 10.1108/mbe-09-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Creation of value for business from the importance-performance analysis: the case of health clubs

Abstract: Purpose The blue ocean strategy refers to how rebuilding the inputs that customers value in the designing of a new value curve fundamentally requires a four field of action structure: reduce, eliminate, create and raise. However, this does not propose a methodology to identify these fields of action. Hence, the purpose of this study is to present importance-performance analysis (IPA), as a support tool to identify these fields of action given their relevance and utility to managers. Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
8
0
3
Order By: Relevance
“…The interviews provided detailed data, accepting the cleanliness as the most influential tangible element. Considering previous research, the importance of clean environments, specifically in locker rooms, is evident [44,48,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…The interviews provided detailed data, accepting the cleanliness as the most influential tangible element. Considering previous research, the importance of clean environments, specifically in locker rooms, is evident [44,48,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Presenting results on the performance-interest grid facilitates management's interpretation of data and improve its usefulness in making strategic marketing decisions [20]. The IPA is designed to compare average scores on the 'perceived importance' of various features with 'satisfaction ratings' that correspond to using a two-dimensional grid [20]- [23]. This grid will classify mean scores into four categories to aid data interpretation and assess priority management: 'maintain good work', 'concentration here', 'low priority', and 'excessive likelihood', allowing management to identify areas of highest concern that warrant limited use of funds [22]- [24].…”
Section: Methodsmentioning
confidence: 99%
“…In the scope of fitness centres, the studies found in the literature have been more focused on the problems of members and have focused mainly on themes such as: growth determinants, Carvalho et al (2013), consumer satisfaction, quality of service and value creation (Barros and Gonçalves, 2009;Pedragosa and Correia, 2009;Pedragosa et al, 2015;Polyakova and Mirza, 2016;Vieira et al, 2019), segmentation of partners (Teixeira and Correia, 2009), a analysis of the partners' intentions to recommend fitness centres (Gonçalves et al, 2014), human resources (Vick and Cunningham, 2018;Wright and Cunningham, 2017) and abandonment/retention (Rodr ıguez Cañamero, 2019;Rodriguez-Canamero et al, 2018;San Emeterio et al, 2016).…”
Section: Garciamentioning
confidence: 99%
“…Barros and Gonçalves (2009) analyses individual satisfaction with fitness centres with the results demonstrating how almost all of the attributes measured contribute towards satisfaction. Furthermore, in terms of the quality of services, Vieira et al (2019) apply the importance-performance methodology in order to identify and evaluate the attributes of service quality that need raising, reducing or eliminating. Wright and Cunningham (2017) examine the influence of disability status among job applicants on stereotype attributions and personnel decisions.…”
Section: Garciamentioning
confidence: 99%